2017
DOI: 10.1038/s41598-017-14138-w
|View full text |Cite|
|
Sign up to set email alerts
|

Acute Psychological Stress Disrupts Attentional Bias to Threat-Related Stimuli

Abstract: The present study investigated the effect of acute stress on attentional bias to threat using behavioral and ERP methods. Sixty-two male participants were randomly assigned to a stress condition (Trier Social Stress Test) or a control condition. To examine the impact of stress-induced cortisol on attentional bias to threat, participants in the stress group were split into Low- and High cortisol responders. All participants were then administered a modified dot probe task in which the cues were neutral and angr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 53 publications
3
19
0
1
Order By: Relevance
“…A study with combined SNS and HPA axis activation revealed an attentional bias toward threat-related stimuli in the placebo group, but not after yohimbine or hydrocortisone administration, nor its combination (Vasa et al, 2009). Similar results have been shown with psychosocial stress induction (Jiang et al, 2017). However, another study reported an attentional bias towards negative emotional stimuli after psychosocial stress (Roelofs et al, 2007).…”
Section: Introductionsupporting
confidence: 53%
“…A study with combined SNS and HPA axis activation revealed an attentional bias toward threat-related stimuli in the placebo group, but not after yohimbine or hydrocortisone administration, nor its combination (Vasa et al, 2009). Similar results have been shown with psychosocial stress induction (Jiang et al, 2017). However, another study reported an attentional bias towards negative emotional stimuli after psychosocial stress (Roelofs et al, 2007).…”
Section: Introductionsupporting
confidence: 53%
“…Thus, the positions of the electrodes may have deviated slightly, introducing additional noise into the predictive models. In addition, a systematic evaluation and control of the participant's general cognitive state should have been conducted, as it could substantially affect the emotional ERP responses (Jiang et al, 2017). Further studies are necessary to elucidate these issues, especially focusing on the participants with low test-retest reliabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the positions of the electrodes may have deviated slightly, introducing 306 additional noise into the predictive models. In addition, a systematic evaluation and 307 control of the participant's general cognitive state should have been conducted, as it 308 could substantially affect the emotional ERP responses (Jiang et al, 2017). Further 309 studies are necessary to elucidate these issues, especially focusing on the participants 310 with low test-retest reliabilities.…”
Section: Performances 276mentioning
confidence: 99%